THE EFFECT OF PROFITABILITY AND TAX PLANNING ON PROFIT MANAGEMENT MODERATED BY MANAGERIAL OWNERSHIP - Rinda Wulandari; Alfiati Silfi; Riska Natariasari (Jurnal Al-Iqtishad, 2024)
This study aims to determine and analyze the effect of Profitability and Tax Planning on Earnings Management with Managerial Ownership as a moderating variable. The population in this study was financial sector companies listed on the Indonesia Stock Exchange for the 2018-2021 period, of which there were 99 companies. The sample consisted of 21 companies selected through the purposive sampling method. This study used the secondary data obtained from the company's annual report. The data analysis method used Multiple Linear Regression Analysis and Moderation Regression Analysis (MRA) with the IBM SPSS 26.0 program. The results showed that Profitability and Tax Planning affect Earnings Management. Managerial Ownership can moderate the effect of Profitability on Earnings Management, but Managerial Ownership cannot moderate the effect of Tax Planning on Earnings Management.